1994
DOI: 10.1007/bf02599054
|View full text |Cite
|
Sign up to set email alerts
|

Screening for sickle-cell trait in the emergency department

Abstract: Most black patients of childbearing age presenting to the ED have heard of sickle-cell anemia and know that it runs in families, but few know their own trait status. Until access to primary care providers is improved, ED physicians who care for patients at risk for sickle-cell trait have an obligation to ask them about prior screening and either screen them or refer them for screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…Similar to previous research, the current study found that a majority of focus group participants did not know their personal SCT status or that of their spouse/partner and children (Midence et al 1994;Wright et al 1994). Fortytwo percent of the 35 participants knew their personal SCT status.…”
Section: Knowledge Of Sickle Cell Trait Statussupporting
confidence: 83%
See 2 more Smart Citations
“…Similar to previous research, the current study found that a majority of focus group participants did not know their personal SCT status or that of their spouse/partner and children (Midence et al 1994;Wright et al 1994). Fortytwo percent of the 35 participants knew their personal SCT status.…”
Section: Knowledge Of Sickle Cell Trait Statussupporting
confidence: 83%
“…Research among African-Americans indicates this population perceives SCD to be a serious disease and SCT screening an important intervention. However, studies have consistently demonstrated a lower than desired uptake of SCD education, inadequate knowledge regarding personal and family trait status, and a low perceived susceptibility of giving birth to a child with the disease (Acharya et al 2009;Gustafson et al 2007;Kladny et al 2005;Midence et al 1994;Treadwell et al 2006;Wright et al 1994). In this study, we examined general attitudes and beliefs regarding genetics and genetic testing including prenatal testing and newborn screening among a unique sample of African-American adults; we used this information as the foundation to more specifically assess attitudes and beliefs regarding SCD and perceived barriers to SCD education and awareness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Like in our study, Gallo, Jae, and Darbari found a lack of awareness of IVF/PGT but a desire for more information once it was introduced. Consistent with the general population, 17,18,26,27 8 or via other medical evaluation. As previously stated, NCAA-mandated SCT testing has been criticized as a lost opportunity for not requiring genetic counseling for those with SCT.…”
Section: Discussionmentioning
confidence: 98%
“…We have demonstrated a difference in awareness of SCT status between men and women that has previously been reported in the literature. Wright et al 12 studied a convenience sample of 147 African-Americans attending and Accident and Emergency Department. Only 31% claimed to be aware of their SCT status and women were more likely than men to report that they knew their SCT status.…”
Section: Discussionmentioning
confidence: 99%